2016
DOI: 10.20344/amp.7411
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimagem e Biomarcadores no Prognóstico Funcional de Doentes com Acidente Vascular Cerebral

Abstract: RESUMOIntrodução: O acidente vascular cerebral é uma das principais causas de mortalidade e morbilidade em todo o mundo, associando-se a considerável incapacidade funcional. Atualmente sabe-se que tanto técnicas de neuroimagem como determinados biomarcadores fornecem informações úteis acerca da etiologia, decisão terapêutica, follow-up e prognóstico em doentes com acidente vascular cerebral isquémico. Assiste-se, porém, a um interesse particular na previsão do prognóstico vital em detrimento do prognóstico fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…De maneira geral, muitos estudos estão sendo conduzidos, mas eles ainda se mostram insuficientes para predizer a recuperação funcional, uma vez que um modelo de predição reprodutível e sensível não foi construído ou alcançado [24][25][26].…”
Section: Discussionunclassified
“…De maneira geral, muitos estudos estão sendo conduzidos, mas eles ainda se mostram insuficientes para predizer a recuperação funcional, uma vez que um modelo de predição reprodutível e sensível não foi construído ou alcançado [24][25][26].…”
Section: Discussionunclassified
“…As a consequence, the inclusion of lesion size in predictive models of outcome has the potential to improve stratification of samples and increase the power for effective detection in trials of acute therapies and of rehabilitative strategies in ischemic stroke. The evaluation of stroke volume and localization when combined with NIHSS showed potential predictive value, which might be further improved by several biomarkers, namely the S100 calcium-binding protein B, C-reactive protein, matrix metalloproteinases, and cerebral natriuretic peptide [34]. …”
Section: Structural Imagingmentioning
confidence: 99%
“…In recent years, the literature has shown that the presence of certain markers in the human body can directly influence stroke survivor prognoses, either positively or negatively. Even though some markers may act predictively, it is not yet known whether an individual marker -or a group of markers, for that matter -acting in isolation have absolute precision in patient prognoses [9]. In addition, these markers, which act as identification tools, are agents whose levels can be observed through experimental measurements that signal the presence of a pathological abnormality or disease in the organism, including a response to a particular pharmacological agent.…”
Section: Introductionmentioning
confidence: 99%